Electromagnetic interference shielding in X-band with aero-GaN. (3rd June 2019) - Dragoman, Mircea; Braniste, Tudor; Iordanescu, Sergiu; Aldrigo, Martino; Raevschi, Simion; Shree, Sindu; Adelung, Rainer; Tiginyanu, Ion
Abstract: We investigate the electromagnetic shielding properties of an ultra-porous lightweight nanomaterial named aerogalnite (aero-GaN). Aero-GaN is made up of randomly arranged hollow GaN microtetrapods, which are obtained by direct growth using hydride vapor phase epitaxy of GaN on the sacrificial network of ZnO microtetrapods. A 2 mm thick aero-GaN sample exhibits electromagnetic shielding properties in the X-band similar to solid structures based on metal foams or carbon nanomaterials. Aero-GaN has a weight four to five orders of magnitude lower than the weight of metals.